Comparison of the Effectiveness of Schema Therapy and Cognitive–Behavioral Therapy on Distress Tolerance in Maladjusted Couples - Saroukhani, Fatemeh; Shafiabadi, Abdollah; Ghodrati, Sima (KMAN Counseling & Psychology Nexus, 2026)
The present study aimed to compare the effectiveness of schema therapy and cognitive–behavioral therapy (CBT) on distress tolerance in maladjusted couples. This applied research was conducted using a quasi-experimental design with pretest–posttest and a control group. The statistical population consisted of all couples who referred to psychology clinics in District 2 of Tehran during the first half of 2025. A sample of 45 couples was selected through convenience sampling and randomly assigned to three groups: schema therapy, cognitive–behavioral therapy, and control. Following the withdrawal of one couple from the cognitive–behavioral therapy group, data analysis was conducted on 44 couples. Research instruments included the Emotional Distress Tolerance Questionnaire, which was administered at three stages: pretest, posttest, and a two-month follow-up. The schema therapy group received ten intervention sessions based on Young’s model, including identification of maladaptive schemas, coping styles, and emotional restructuring techniques (Young, 2003). The cognitive–behavioral therapy group participated in ten sessions focusing on communication skills training, cognitive restructuring, stress management, and modification of dysfunctional patterns (Beck, 2011). No intervention was implemented for the control group. Data were analyzed using repeated measures analysis of variance. The results indicated that both interventions significantly improved couples’ distress tolerance; however, schema therapy demonstrated significantly greater effectiveness than cognitive–behavioral therapy, and its effects remained more stable at the follow-up stage. Based on these findings, it can be concluded that the deeper, emotion-focused, and core-level interventions characteristic of schema therapy play a more substantial role in enhancing distress tolerance among maladjusted couples.